Imaging in gynecological disease (13): clinical and ultrasound characteristics of endometrioid ovarian cancer. (4th October 2018) - Moro, F.; Magoga, G.; Pasciuto, T.; Mascilini, F.; Moruzzi, M. C.; Fischerova, D.; Savelli, L.; Giunchi, S.; Mancari, R.; Franchi, D.; Czekierdowski, A.; Froyman, W.; et al.
ABSTRACT: Objective: To describe the clinical and ultrasound characteristics of ovarian pure endometrioid carcinomas. Methods: This was a retrospective multicenter study of patients with a histological diagnosis of pure endometrioid carcinoma. We identified 161 patients from the International Ovarian Tumor Analysis (IOTA) database who had undergone preoperative ultrasound examination by an experienced ultrasound examiner between 1999 and 2016, and another 78 patients from the databases of the departments of gynecological oncology in the participating centers. All tumors were described using IOTA terminology. In addition, one author reviewed all available ultrasound images and described them using pattern recognition. Results: Median age of the 239 patients was 55 years (range, 19–88 years). On ultrasound examination, two (0.8%) endometrioid carcinomas were described as unilocular cysts, three (1.3%) as multilocular cysts, 37 (15.5%) as unilocular‐solid cysts, 115 (48.1%) as multilocular‐solid cysts and 82 (34.3%) as solid masses. Median largest tumor diameter was 102.5 mm (range, 20–300 mm) and median largest diameter of the largest solid component was 63 mm (range, 9–300 mm). Papillary projections were present in 70 (29.3%) masses. Most cancers (188 (78.7%)) were unilateral. In 49 (20.5%) cases, the cancer was judged by the pathologist to develop from endometriosis. These cancers, compared with those without evidence of tumor developing from endometriosis, more often manifested papillary projections on ultrasound (46.9% (23/49) vs 24.7% (47/190)), were less often bilateral (8.2% (4/49) vs 24.7% (47/190)) and less often associated with ascites (6.1% (3/49) vs 28.4% (54/190)) and fluid in the pouch of Douglas (24.5% (12/49) vs 48.9% (93/190)). Retrospective analysis of available ultrasound images using pattern recognition revealed that many tumors without evidence of tumor developing from endometriosis (36.3% (41/113)) had a large central solid component entrapped within locules, giving the tumor a cockade‐like appearance. Conclusions: Endometrioid cancers are usually large, unilateral, multilocular‐solid or solid tumors. The ultrasound characteristics of endometrioid carcinomas developing from endometriosis differ from those without evidence of tumor developing from endometriosis, the former being more often unilateral cysts with papillary projections and no ascites. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.